2009
DOI: 10.1074/jbc.m109.049577
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of His465 Alters the pH-dependent Spectroscopic Properties of Escherichia coli Glutamate Decarboxylase and Broadens the Range of Its Activity toward More Alkaline pH

Abstract: Glutamate decarboxylase (GadB) from Escherichia coli is a hexameric, pyridoxal 5-phosphate-dependent enzyme catalyzing CO 2 release from the ␣-carboxyl group of L-glutamate to yield ␥-aminobutyrate. GadB exhibits an acidic pH optimum and undergoes a spectroscopically detectable and strongly cooperative pH-dependent conformational change involving at least six protons. Crystallographic studies showed that at mildly alkaline pH GadB is inactive because all active sites are locked by the C termini and that the 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…The intrinsic fluorescence of tryptophans and coenzyme has been previously exploited to investigate structural and dynamic features of some PLP-dependent enzymes and their modification upon binding of substrates, inhibitors, and regulatory molecules [2530]. In GSAM, both PLP and PMP are fluorescent upon excitation in either the UV or visible range of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic fluorescence of tryptophans and coenzyme has been previously exploited to investigate structural and dynamic features of some PLP-dependent enzymes and their modification upon binding of substrates, inhibitors, and regulatory molecules [2530]. In GSAM, both PLP and PMP are fluorescent upon excitation in either the UV or visible range of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the emission band of PLP-GSAM excited at 320 and 330 nm appears to have a slightly red-shifted (by 3-4 nm) peak wavelength with respect to PMP-GSAM, and is definitely more asymmetric, being broader on the low energy side of the emission spectrum (the ratio of emission intensity at 390 and 500 nm is about 5, compared to more than 20 for PMP-GSAM). Furthermore, differently from PMP-GSAM, when PLP-GSAM is excited at 340 nm, the main emission band is slightly decreased in intensity and is accompanied by a shoulder at about 500 nm (Figure 3(c)), most likely due to direct excitation of the high energy tail of the absorption band of PLP ketoenamine tautomer [30, 33, 34]. The presence of a discrete emission at around 500 nm could also originate from the ketoenamine tautomer that forms in the excited state following proton transfer from the 3 ' -OH group to the imine nitrogen [35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the eight residues listed above, which are shared with group II decarboxylases, the concurrent presence of the residues listed in bold in Table (numbering refers to E. coli GadB) may be regarded as the signature for bacterial GAD. The latter residues play different roles: Asp86* (*from the neighbouring subunit in the functional dimer), with its side‐chain tilted towards the active site in the open conformation, interacts with the γ‐carboxylate of the substrate glutamate; Glu89* in the low‐pH structure is not far away from Asp86*, from which in the neutral‐pH structure it points in opposite direction (Capitani et al ., ); Gln163 with its side‐chain alkyl portion acts as stacking residue for the PLP ring; Thr62 side chain hydroxyl and Phe63 amide nitrogen provide additional hydrogen bonds to the γ‐carboxylate of the substrate; Phe63 with its side‐chain ring plays also an important role in preventing the binding of the α‐carboxylate of glutamate to Arg422 (corresponding in sequence and spatial position to the arginine side‐chain which binds the α‐carboxylate of the amino acid substrate in PLP‐dependent transaminases); His275, preceding the PLP‐binding residue Lys276, is critical for keeping the cofactor in place by making an hydrogen bond with an oxygen of the PLP phosphate group via its side‐chain τ nitrogen (Tramonti et al ., ; Capitani et al ., ); Tyr305* and Leu306*, at the tip of the β‐hairpin 300–313, interact with residues 461–463 at the C‐terminus in the inactive form; Tyr305* may also be involved in protonating the substrate during the decarboxylation reaction, similarly to Tyr332 in Dopa decarboxylase (Bertoldi et al ., ); His465 is responsible for GadB auto‐inhibition via formation of an aldamine, an entirely novel species originating from the reaction of His465 side‐chain τ nitrogen with the Lys276‐PLP Schiff base (Gut et al ., ; Pennacchietti et al ., ).…”
Section: Functional and Structural Insights Into E Coli Gadbmentioning
confidence: 97%
“…in reconstituted proteoliposomes) studies show to be active only at pH ≤ 5.5 (Richard and Foster, ; Ma et al ., ). The activity profile of GadC as a function of pH remarkably resembles that of GadB (Pennacchietti et al ., ; Ma et al ., ). Despite the different function, GadB and GadC not only share an almost overlapping activity profile, but also adopt similar mechanisms to control their activity in the cell.…”
Section: Functional and Structural Insights Into E Coli Gadcmentioning
confidence: 97%
“…This makes it possible to change enzyme specificities like its activity, thermo stability and pH dependency (Moreau et al, 1994). Previous studies indicated that C-terminal truncation or mutation of His245 residue enable the enzyme to be active at the wider range of pH (Pennacchietti et al, 2009;Yu et al, 2012). For industrial applications and large-scale production a special enzyme needs to be more thermo-stable and highly activated (Akanuma et al, 1998).…”
Section: Introductionmentioning
confidence: 98%